5y3 - 125y =
5y(y - 5)(y + 5)
factor pair = 1512,1 factor pair = 756,2 factor pair = 504,3 factor pair = 378,4 factor pair = 252,6 factor pair = 216,7 factor pair = 189,8 factor pair = 168,9 factor pair = 126,12 factor pair = 108,14 factor pair = 84,18 factor pair = 72,21 factor pair = 63,24 factor pair = 56,27 factor pair = 54,28 factor pair = 42,36
Limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals", "squared", "cubed". The answer is probably 3, the highest power of y in the expression, but it depends on what symbol is before "6y".
I usually start from the bottom - is 2 a factor, yes indeed. Then start over. Is 2 a factor, yes. Start over. Is 2 a factor, yes. Is 2 a factor, no. Is 3 a factor, no. is 4 a factor, no. Done.2, 2, 2, 5
The following are the factor pairs of 950 factor pair = 950,1 factor pair = 475,2 factor pair = 190,5 factor pair = 95,10 factor pair = 50,19 factor pair = 38,25
x = 5y3/6
45 - triode power amplifier 80 - fullwave rectifier 125A - - can't find data 1C5 - pentode power amplifier 5Y3 - equivalent to 80 5U4 - higher-rated version of 80/5y3 12SA6 - - can't find data - did you mean *12sa7* pentagrid converter
LCM(5y3, 25y6) = 25y6
Tube Socket ___ octal n 4pin
y to the six is common, so it becomes y^3(y^3 - 125). Then we use difference of cubes ((a-b)(a^2 - 2ab + b^2)), so it becomes y^3(y-5)(y^2 + 5y + 25). Since we cannot factor out that last quadratic part, this concludes the factoring process and we end up with that last line as our answer.
Courtyard Creations customer service 150 Marycroft Ave Woodbridge, Ontario, Canada, L4L 5Y3 1-877-539-7436
Just to clarify: (12x4y2)/(10x3y5). Subtract the exponents of x: 4-3 = 1. And y exponents: 2-5 = -3. Then 12/10 simplifies to 6/5, so we have (6x)/(5y3)
(1/2y3)2(.5y3)2Multiply each term's exponent by 2 (remember that .5 = .51).52y(6).25y6 or 1/4y6
Y³-4y²-12y = y(y - 6)(y + 2) 3x³+30x²+75x = 3x(x + 5)2 5yto5-80y³ = 5y3(y + 4)(y - 4) 24to5-18y³ = 6y3(4y2 - 3) 25x to the 6th - 64 = (5x3 + 8)(5x3 - 8) 27xt³+343 = (3x + 7)(9x2 - 21x + 49) X³-64 = (x - 4)(x2 + 4x + 16)
4x + y53 is an expression. Thanks to the rubbish browser used by this site for posting question, most mathematical symbols have been stripped out. There is, therefore, no equality not inequality sign and so there is nothing which can be solved.